An architecture-centric and ontology-based approach to cross-domain interoperability of health information systems for diabetes care (2015)
This doctoral work focuses on the improvement of collaboration between the different actors involved in the care of patients suffering type 2 diabetes mellitus. This chronic disease causes more than 4,9 million deaths each year and high costs to health systems. Around 7% of the Colombian population older than 30 years is affected by this disease. An important characteristic of this health problem is that it requires a multi-disciplinary care team. This is because of the different aspect of life style of the persons impacting that disease and the multiple complications managed by different medical specialties. Another important aspect is that the need of active collaboration of the patient, performing self-care and changing his life style. From the computational perspective, information systems interoperability is a crucial challenge. Specially, interoperability between Personal Health Record systems (PHRs) and Electronic Health Record systems (EHRs) is required. PHRs are managed by the patient during self-care and allow managing information about his health (e.g. calorie ingests, physical activity, glucose levels). There is a lot of research trying to solve the interoperability problem from technical perspectives, but ignoring the actor differences and the information semantics. This work intends to consider these aspects and to achieve interoperability at a more comprehensive level.